2017
DOI: 10.1016/j.ekir.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of STAT3 Signaling Reduces IgA1 Autoantigen Production in IgA Nephropathy

Abstract: IntroductionIgA nephropathy is a chronic renal disease characterized by mesangial immunodeposits that contain autoantigen, which is aberrantly glycosylated IgA1 with some hinge-region O-glycans deficient in galactose. Macroscopic hematuria during an upper respiratory tract infection is common among patients with IgA nephropathy, which suggests a connection between inflammation and disease activity. Interleukin-6 (IL-6) is an inflammatory cytokine involved in IgA immune response. We previously showed that IL-6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 70 publications
(95 reference statements)
1
41
0
Order By: Relevance
“…IL-6 canonical signaling utilizes the JAK/STAT3 pathway [49][50][51], a critical interface between autoimmunity and immune deficiency. Recently, we determined that abnormal IL-6-induced signaling through IL-6 receptor-gp130 and JAK2/STAT3 pathway was associated with elevated synthesis of Gd-IgA1 by IgA1-producing cells from patients with IgAN but not HC [26]. Loss of STAT3 signaling disrupts the mucosal barrier in disease such as Crohn's disease, resulting in epithelial expression of the IL-6-like cytokine Upd3, leading to activation of JAK/STAT signaling, differentiation of cells that form the progenitor cells niche, and abnormal proliferation of progenitor cells [52].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…IL-6 canonical signaling utilizes the JAK/STAT3 pathway [49][50][51], a critical interface between autoimmunity and immune deficiency. Recently, we determined that abnormal IL-6-induced signaling through IL-6 receptor-gp130 and JAK2/STAT3 pathway was associated with elevated synthesis of Gd-IgA1 by IgA1-producing cells from patients with IgAN but not HC [26]. Loss of STAT3 signaling disrupts the mucosal barrier in disease such as Crohn's disease, resulting in epithelial expression of the IL-6-like cytokine Upd3, leading to activation of JAK/STAT signaling, differentiation of cells that form the progenitor cells niche, and abnormal proliferation of progenitor cells [52].…”
Section: Discussionmentioning
confidence: 99%
“…The Gd-IgA1 concentration was expressed in units (U) defined as the ratio of OD determined for the individual sample and the OD for a standard Gd-IgA1 (Ale) myeloma protein. Specifically, 100 U was defined as the OD of 100 ng of the standard Gd-IgA1 protein [26].…”
Section: Gd-iga1 Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Such mechanisms could contribute to the etiology of synpharyngitic hematuria. Recently, it was reported that modulation of IL-6-triggered intracellular signaling by STAT3 could alleviate Gal deficiency of IgA1 [16]. …”
Section: Introductionmentioning
confidence: 99%